Imagined Libya: geopolitics of the margins - Luca Raineri (L’Année du Maghreb)
Whether referring to the artificiality of its (post-)colonial construction or to the fragmentation of its sovereignty since 2011, the weakness of Libya’s statehood is a recurrent theme in policy and scholarly discourses. Scholars of history and international politics have expanded the framework to apprehend the processes of state (de/)formation underpinning Libya’s fragilities beyond the problematic “failed state” paradigm to accommodate longue-durée and multi-scalar perspectives. Building on these advances, yet noting the need for a more consistent use of social constructivist lenses, the article adopts the perspective of critical geopolitics to explore the spatial discourses and imaginaries, both domestic and imported, that across history have shaped “Libya”, as well as its internal constituents and its external environment, through processes of identification, othering and belonging. Given the diversity of uses – and abuses – connoting geopolitics and its critical variants, the first section of the article clarifies the meaning, relevance and methodology of the critical geopolitics approach herein employed. It is argued that Libya sits at the intersection of rival geopolitical imaginaries and competing spheres of influence that overlap and collide here. The subsequent sections analyze geopolitical discourses from different sources to offer a review of some important spatial imaginaries that have contributed to representing, constituting and apprehending Libya as a subject and an object of international politics: ancient geography’s environmentalism; Italy’s imperial colonialism; Gaddafi’s pan-Arabism and, later, pan-Africanism; and Turkey’s pan-Ottomanism.Before modern colonisation, the imaginary of (today’s) Libyan territory was long apprehended through the dichotomy between urban (hadari) and rural (badawi) spaces, with the political and normative centre of gravitation oscillating from the former (during the Arab and later Ottoman hegemony) to the latter (during the rise of the Sanussi order). During the Italian colonisation, Libya was subsumed in Italy’s Mediterranean projections, whether as a necessary “fourth shore” to Italy’s expansion in its “own” Lebensraum, or as a bridge welding Europe and Africa within a unitary geopolitical entity called Eurafrica. Gaddafi’s pan-Arabism and pan-Africanism combined short-term political opportunism with a more ambitious attempt to challenge (neo-)colonial geopolitical imaginaries about the country’s identity and belonging, and its related security priorities. Yet they both contributed to the abusive manipulation of domestic ethnic cleavages, the weaponization of (the research into) the country’s history, and the progressive de-legitimation of the regime. Today, Libya has acquired a prominent role in Turkey’s geopolitical imaginary. After more than a century of substantial disregard, the rise of a pan-Ottoman geopolitical repertoire in Turkey and the nationalistic emphasis on the redeeming of the vatan (homeland) provide the key for interpreting Turkey’s resurrecting interest in Libya, and the justification of its military intervention vis-à-vis Ankara’s domestic audiences. The exploration of these prominent geopolitical imaginaries on, by and about Libya highlights the tensions, intersections, and divergences underpinning different interpretations of the same territory. The enduring legacy of competing geopolitical imaginaries points to a plausible constitutive factor laying at the root of the polarisations and conflict dynamics that endanger the stability and survival of the Libyan state. Unearthing the competing geopolitical imaginaries on Libya can thus help illuminate the divergent approaches of the international actors intervening in the country, and those of their Libyan proxies struggling for recognition, be they Turkey’s allies, or Libya’s armed actors posturing as Europe’s gatekeepers in the contemporary iterations of the ambivalent geopolitical imaginary of Eurafrica. A critical geopolitics approach thus helps challenge the obsolete yet widespread view of Libya’s marginality in the international system, by unsettling reified spatial assumptions about the partition, position and constitution of Libya’s state. It is precisely Libya’s position at the periphery of rival geopolitical imaginaries and asserted spheres of influence that makes of it a crossroad of strategic vectors, a hotspot of collisions, and therefore a centre of concern.